Patient’s satisfaction with prosthetic devices - Poljak-Guberina, Renata (Array, 2005)
The purpose of the paper was to ascertain the factors which affect the satisfaction of patients with the prosthetic therapy. The purpose of the paper was also to ascertain if there are common factors characteristic for patients dissatisfied with the prosthetic therapy although the specialist appraises it as objectively successful. 52 patients of the Clinical Institute for Rehabilitation and Orthopedic Devices were participating in the research, to which, after unsuccessful surgical-prosthetic rehabilitation, reamputation and prosthetic provision was carried out, which was appraised successful by the doctor. It was endeavored to appraise to what extent the appraisal by the doctor corresponds to patient’s satisfaction. On the basis of the questionnaire elaborated specifically for this research and the statistical processing, it was concluded that where the doctor appraised the prosthetic therapy as successful, the same opinion was shared by the majority of the patients (92.3%). Patients are similarly satisfied with the function and the esthetic quality of the prosthesis (73%). The reason why 7.7% of patients are dissatisfied in cases when the doctor considers that there are no objective reasons for that should be sought in non-medical factors. The age, the education, the marital status, the income state, the size of the residence and the regional affiliation do not have a significant influence on the satisfaction of patients with the prosthesis (p>0.05). Patients with a minor handicap achieve satisfaction with the prosthetic therapy faster, as well as the right-handed persons if the prosthesis on the right-hand extremity is in question (p<0.05). This investigation showed that the responsibility of not wearing prosthetic aids, both orthopedic, and dental prostheses, couldn’t be only neuroticism by prosthetic patients, because that connection is not statistically significant (p<0.09).